IMPACT OF BODY MASS ON THE MOTOR ABILITIES MANIFESTATION IN STUDENTS OF DIFFERENT AGES - T. Marinov (Trakia Journal of Sciences)
Studying the students’ body weight is a problem of the present day primarily associated with assessing their health status. However, few scientific studies reveal its impact on students’ abilities to acquire physical education content. That is why we set ourselves the aim to establish the influence of students’ body mass on their motor abilities manifestation. Methods: Using the standard for our education system test battery, we measured the height, weight, and physical ability of 218 boys and girls in the 4th, 7th, and 12th grades from 3 schools in Sofia. We processed the results using correlation analysis (Pearson's r). Results: We found that being overweight in 4th-grade boys and girls had a negative impact on the manifestation of all the motor skills studied. During puberty (in the 7th grade), the higher body mass index makes it difficult for students to manifest their speed and strength. In the 12th grade, it favours the manifestation of lower limb strength and endurance in girls and dramatically harms the boys’ manifestation of speed and agility. Conclusion: As a result of the correlation between body mass and motor skills we derived, teachers can plan more accurately the means and methods of physical training in the lesson for students of different ages.